Phosphoric acid doped polysulfone membranes with aminopyridine pendant groups and imidazole cross-links - Hink, Steffen; Elsoe, Katrine; Cleemann, Lars Nilausen; Henkensmeier, Dirk; Jang, Jong Hyun; Kim, Hyoung-Juhn; Han, Jonghee; Nam, Suk-Woo; Li, Qingfeng (Pergamon Press Ltd., 2015)
Udel polysulfone based membranes with 4-aminopyridine pendant groups and cross-linking imidazole units are synthesized in a simple two step reaction. The ratio of 4-aminopyridine and imidazole is varied and the materials are extensively characterized. The average phosphoric acid uptake (in 85 wt% PA) ranges between 90 wt% and 452 wt% depending on the ratio of 4-aminopyridine and imidazole and the membranes show good proton conductivity of up to 65 mS cm(-1) at 160 degrees C under non-humidified conditions. The applicability of these materials as a polymer electrolyte membrane was proven by single cell tests at 130 degrees C. The relationships between PA uptake, chemical composition and mechanical stability are reported. Proton conductivity and mechanical properties only depend on the phosphoric acid content, which, however is a function of the chemical composition. (C) 2015 Elsevier Ltd. All rights reserved.